1996
DOI: 10.1111/j.1748-5827.1996.tb01928.x
|View full text |Cite
|
Sign up to set email alerts
|

Sedative effects of romifidine in the dog

Abstract: The sedative and physiological effects of intravenous romifidine at 0, 20, 40, 80 and 120 micrograms/kg were investigated in five clinically normal adult male beagle dogs in a blind study using a Latin square design. Following the injection of romifidine, the dogs became ataxic and stood with a wide-based stance, they exhibited signs of skeletal muscle relaxation and their heads were lowered. All the dogs became recumbent and there was a reduction in the heart and respiratory rates. Increasing the dose from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
69
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 12 publications
13
69
4
Order By: Relevance
“…This result agrees with the results obtained by England and others (1992), Scrollavezza and Zanichelli (1993) and Hamm and others (1995) in horses, and by Vainio and others (1989), England and others (1996b) and Lemke (1999) in dogs, who reported that the degree of muscular relaxation induced by romifidine was similar to or slightly less than that induced by other α 2 -adrenoceptor agonists.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result agrees with the results obtained by England and others (1992), Scrollavezza and Zanichelli (1993) and Hamm and others (1995) in horses, and by Vainio and others (1989), England and others (1996b) and Lemke (1999) in dogs, who reported that the degree of muscular relaxation induced by romifidine was similar to or slightly less than that induced by other α 2 -adrenoceptor agonists.…”
Section: Discussionsupporting
confidence: 92%
“…There have been several studies of its use in dogs (England and others 1996a, b, England and Hammond 1997, England and Thompson 1997, Lemke 1999, 2001, Pypendop and Verstegen 2001, Melissa and others 2002), but few reports of its use in cats (Gomez-Villamandos and others 1994, Verstegen and others 1995, Selmi and others 2004, Belda 2005). …”
mentioning
confidence: 99%
“…There was no effect following placebo administration. These events were similar to those observed by England et al (1996b).…”
Section: Discussionsupporting
confidence: 89%
“…These adverse effects have been observed frequently and reported following administration of other a2 adrenoceptor agonists (Vainio 1989;England et al 1996b).…”
Section: Discussionmentioning
confidence: 96%
“…Romifidine is an α 2‐adrenergic agonist sedative used in small animals, with similar sedative actions to other drugs of its pharmacological group (England et al. , 1996a).…”
Section: Cardiovascular Variables Of Seven Dogs Anaesthetized With Prmentioning
confidence: 99%